Sports Activity Analysis in Identifying Student Behavior During Sports - Cendra, Romi; Gazali, Novri; Rapindo, Rapindo; Piranda, Muhammad Piqih (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to identify sports activities in shaping students' behavior when exercising. The research method used is ex post facto with quantitative descriptive analysis. The population of the study was students of SMP Negeri 6 Siak Hulu Kampar Riau with samples taken randomly (random sampling) based on a questionnaire distributed to students via google form, so that the total number of samples taken for students who filled out the questionnaire was 175 people. The research instrument used a questionnaire to see students' habits in sports activities and a Likert scale questionnaire to see students' behavior and/or character when exercising. The data analysis used was percentage test analysis. The results of the data analysis showed that the sports activities of students of SMPN 6 Siak Hulu based on their routine of doing sports in a week were categorized as almost always and very often doing sports activities as many as 69 people with a percentage of 39.01%, while the category was very rare and almost never doing sports activities in a week was 106 people with a percentage of 61.01%. Meanwhile, the analysis of student behavior during classical sports and/or overall in doing sports activities in a week can be seen from the results, namely the category of strongly agreeing and agreeing in doing sports activities in a week amounted to 78 people with a percentage of 43.33%, while the category of disagreeing and strongly disagreeing amounted to 97 people with a percentage of 56.67%. The importance of a person or student in maintaining and taking time for sports activities, especially if it is done routinely and intensely, because the benefits of a person's routine in doing sports activities in addition to maintaining fitness to become a healthy person, sports can also shape a person's character (attitude and behavior) due to the routine of doing these sports activities.